Balanced Scorecard and Morgan’s organizational metaphors - Pietrzak, Michał (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The aim of the paper is to discuss the concept of the Balanced Scorecard based on some of Morgan’s metaphors. Very popular metaphor that underlines the mainstream way of thinking about organization is the machine metaphor. However, for contemporary organizations facing turbulent environments, such one-sided insight will be insufficient. The BSC offers managers much more complex and comprehensive insight in organizations and reinforce alternative to the mechanistic view images of organizations, namely: organization as organism, organization as information processor and organizations as culture
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 474, s. 106-114
Keywords: Balanced Scorecard; Morgan’s metaphors; images of organizations; Zrównoważona Karta Wyników; metafory Morgana; wizje organizacji